Tumor perivascular cell-derived extracellular vesicles promote angiogenesis via the Gas6/Axl pathway. (1st January 2022) - Huang, Maohua; Liu, Mingqun; Huang, Dandan; Ma, Yanping; Ye, Geni; Wen, Qing; Li, Yong; Deng, Lijuan; Qi, Qi; Liu, Tongzheng; Liu, Xiangning; Chen, Minfeng; et al.
Abstract: Aberrant angiogenesis is a hallmark of cancer and is critically associated with tumor progression. Perivascular cells are essential components of blood vessels, and the role of tumor perivascular cell-derived extracellular vesicles (TPC-EVs) in angiogenesis remains elusive. In the present study, using genetic mouse models and pharmacological inhibitors, we found that ablation of perivascular cells inhibited angiogenesis in allografted colorectal cancer tumors. Further studies demonstrated that TPC-EVs promoted the proliferation, migration, invasion, viability, and tube formation of HUVECs. They also facilitated vessel spouting in rat aortic rings and induced neovascularization in chick chorioallantoic membranes (CAMs). Silencing of Gas6 or blockade of the Axl pathway suppressed TPC-EV-induced angiogenesis in vitro and ex vivo . Moreover, inhibition of the Gas6/Axl signaling pathway impaired TPC-EV-mediated angiogenesis in vivo . Our findings present a deeper insight into the biological functions of TPCs and TPC-EVs in tumor angiogenesis and demonstrate that TPC-EV-derived Gas6 could be an attractive and innovative regulator of tumor angiogenesis. Highlights: Tumor perivascular cell-derived extracellular vesicles (TPC-EVs) promote tumor angiogenesis. TPC-EVs promote tumor angiogenesis by activating the Gas6/Axl signaling pathway in endothelial cells. The EV-Gas6/Axl pathway is a feasible target for antiangiogenic therapy in colorectal cancer.